The Support Educational Commitee Participation in the Pedagogical Approach of an Educational Integration - Fontana Hernández, Angélica (2010)
Educational services are essential to social and economical development of people, mainly to the progress of all sectors of society. Establishing actions that can promote the participation of various social groups is essential to improve their quality of life and building more respectful and fair human rights without any discrimination or exclusion. In recent years, the Costa Rican education system has undergone significant changes due to the pedagogical approach of inclusive education in which students with educational needs may require different support and specialized resources for training and development. For this, the Basic Educational Division of the Center for Teaching and Research in Education, generated a concern of investigating the participation of the Committee of Educational Support in the process of educational integration, thus, determine the functions performed in the educational context, under the rules of the 7600 Equal Opportunity Act for people with disabilities, which is the entity that corresponds to regulate access to education by identifying the support required for students with educational needs and, advice and trains, administrative staff in schools both public and private in the country. In addition, there is also a concern for exploring the role of the Special Education teacher for this Committee, as well as learning the perceptions of teachers and parents about the functions performed by the committee.